Knowledge service supplies and business marketing tasks of higher education institutions - Deés, Szilvia; Szontágh, Krisztina (REGIONAL AND BUSINESS STUDIES, 2011)
When the marketing activities of Hungarian universities are analyzed, it can be concluded that these activities focus almost solely on the marketing of enrollment and neglect any kind of communication with corporations. Yet modern universities have a wider range of tasks than merely education and research. The third objective of universities is to create new knowledge and utilize it: a new entrepreneurial function additional to traditional research and teaching activities. This also influences communication activities, since universities should compete not only for the best students and academics but also for corporate commissions. Also, they should cooperate with industry players, other private R&D institutes, investors, and other universities. The corporate sphere takes the view that universities should contact companies in order to widen cooperation with companies and expand commissions for innovation and that they should acquaint companies with their services, which is likely to require hard work. The establishment of relationships between a corporation and a university depends on people qualified and positioned to take on the task. Personal and face-to-face communications are necessary for effective communication. An element of this communication is analyzed in this study: the appearance of knowledge service supplies on Hungarian university web sites. The study also focuses on the usable knowledge provided by doctoral schools and the websites of Technological Transfer offices established in 2010-2011 through EU tender resources and the connections of these websites. Keywords: innovation, knowledge transfer, technology transfer, university-corporate relationship